Congenital cytomegalovirus virus infection - Rana, PVS (Kathmandu University Medical Journal, 2010)
A 14 months old male child with psychomotor retardation and hypotonia is reported, where computerized axial tomography revealed multiple calcification and ventriculomegaly secondary to cortical atrophy. Investigation suggested the diagnosis of cytomegalovirus infection. Importance of early diagnosis is emphasized as the potential long term sequelae can be prevented or reduced markedly with available therapeutic options. Key words: Congenital; Cytomegalovirus; Psychomotor retardation; Calcification; Ganciclovir; Hyper immune globulin DOI: 10.3126/kumj.v7i2.2709 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 145-148